The analysis of heavy metals content in soil: a case study of total nutrient at Cameron Highlands, Pahang / Aizzul Najmi Amir Hiszam - Amir Hiszam, Aizzul Najmi (Faculty of Plantation and Agrotechnology, 2017)
The purpose of this study was to investigate the concentration of heavy metals in three different location from agricultural areas at Cameron Highlands, namely Kampung Raja, Tanah Rata and Ringlet. The objective of the study conducted was to determine the heavy metals content from 0 cm to 15 cm and 16 cm to 30 cm soil depth, and to clarify which agricultural areas was at the most highest heavy metals content, which were the Aluminium (Al), Iron (Fe), Copper (Cu) and Zinc (Zn) element. Completely Randomized Design (CRD) experimental design was implemented during the experiment sampling. At each selected location, a total of five samples were taken from each soil depth and sum of ten samples for each location respectively. All of the samples taken were analyse by using Aqua Regia method at 3:1 ratio chemical component of Hydrochloric acid and Nitric acid and the sample concentration are then tested by using the Inductively Coupled Plasma (ICP) machine. The data retrieved from conducted experiment was analysed by using Minitab software on One-Way ANOVA calculation method. The experiment outcome proportionally reflect to the objectives, Kampung Raja and Tanah Rata was identified to have high Al content is soil at mean range of 13896-13904 mg/kg and 18918-19652 mg/kg respectively. Highest heavy metals at Ringlet region was identified by Fe content at mean range of 8438.8-8613.8 mg/kg. As the recommendation upon the result obtained from the experiment, the application and usage of pesticide, herbicide, and insecticide should be controlled and following the chemical emission permissible and also as recommended from related local authority at Cameron Highlands.